Selektive Hemmung von Tyrosinkinasen als neues therapeutisches Prinzip in der Onkologie - Hochhaus, Andreas; Lahaye, T.; Kreil, Sebastian; Berger, Ute; Metzgeroth, Georgia; Hehlmann, Rüdiger (Onkologie, 2001)
Selective Inhibition of Tyrosine Kinases - a New Therapeutic Principle in Oncology Tyrosine kinases are enzymes that regulate mitosis, differentiation, migration, neovascularization, and apoptosis. Their spectrum and association with specific malignancies offer multiple targets for therapeutic intervention. Chronic myelogenous leukemia (CML) represents an ideal target for a therapy using a selective inhibitor of the BCR-ABL tyrosine kinase. The 2-phenylpyrimidine derivative STI571 was rationally designed to inhibit ABL and BCR-ABL tyrosine kinase activities through competitive ATP-binding pocket interactions. Phase II data demonstrate hematologic and cytogenetic responses in interferon refractory chronic-phase, accelerated-phase and blast crisis patients. However, long-term observation is needed to confirm that response data result in prolongation of survival. STI571 is being studied in other malignancies, including leukemias characterized by expression of alternate molecular forms of BCR-ABL and those expressing protein tyrosine kinases with ATP-binding pockets structurally similar to ABL, e.g. c-kit and PDGF-R. Gastrointestinal stromal tumor (GIST) cells overexpress the stem cell factor receptor CD117, the product of the proto-oncogene c-kit. Inhibition of c-kit in vivo results in an immediate metabolic change of the tumor cells, detectable by positron emission tomography. Since c-kit overexpression is inhibited in small-cell lung cancer cell lines, a study with STI571 as second-line therapy of c-kit-positive small-cell lung cancer is in progress. Clinical studies are ongoing in malignancies associated with an enhanced activity of the PDGF-R, such as highgrade glioma, prostate cancer and leukemias with rearrangements of PDGF-R. The development of selective tyrosine kinase inhibitors is considered a promising approach for the design of new drugs. Clinical responses to STI571 in various malignancies may stimulate greater interest in the clinical use of tyrosine kinase inhibitors.